Measurement of riskiness of agricultural income - evidence from India’s agrarian economy - Guptaa, Deepa; Ghosh, Bidyut; Neogi, Suvayan (Asian Journal of Agriculture and Rural Development, 2025)
Farmers in developing countries face significant challenges due to price and production fluctuations, which impact their income and well-being. This study focuses on potato and onion farmers in India to estimate the income variability experienced by them. This research applies the Autoregressive Distributed Lag (ARDL) approach to investigate how fluctuations in market prices influence agricultural supply, with an emphasis on both short- and long-term effects. The demand elasticity (ε) for potato is equal to ‒1.32, while for onion, it is 0.54. This study finds that income volatility is a significant issue for potato and onion farmers, which could impact the long-term well-being of the farmers in India. Price fluctuations in agricultural production, combined with lower market prices, pose serious threats to farmers’ income. To reduce risks, the study recommends comprehensive strategies, such as improved price stabilization initiatives, agricultural income insurance, and financial tools like commodity derivatives. In particular, it suggests considering index-based income insurance that provides compensation based on specific indicators, such as regional yield and price changes. These measures can enhance financial security and resilience for Indian farmers facing market uncertainties.